Pediatric Hearing Loss and the Multidisciplinary Approach. The Hearing Disability Team (HDT) Experience - Palma, Silvia; Nascimbeni, Laura; Pecovela, Maria Chiara; Ciorba, Andrea; Pirani, Graziella; Monzani, Daniele; Genovese, Elisabetta (International Journal of Pediatrics and Child Health, 2024)
Hearing loss is among the utmost common disorders in children and a late diagnosis can impact language and cognitive development. With the aim of implementing an early hearing detection program (EHDP), the Emilia Romagna region has officially approved, since 2012, a NHS program distinguishing well babies and NICU children. Aim of this study is to evaluate the results of the application of these regional guidelines through data flow from the Child and Adolescent Mental Health Services (CAMHS). Data of children born between 2012 and 2018 and admitted to the service in the same period were collected, 84 children (56 males,28 females) were enrolled; 65% of the children were taken in charge by CAMHS within the first year of life. Concerning the NHS results, 77 (91%) children resulted fail at the screening test (6 unilateral fails), while the result was not available in one case; 6 children resulted pass. Most cases, 79 (94%), presented bilateral hearing loss. In particular, 14 (17.8%) children had a profound hearing loss, 10 (12.6%) a severe hearing loss, 10 (12.6%) a mild hearing loss (6 were conductive), 22 (27.8%) a moderate hearing loss, and 23 (29.2%) a moderate/severe hearing loss. Finally, 5 resulted affected by unilateral hearing loss (2 profound hearing loss, 3 severe). This study confirmed that regional recommendations about early diagnosis of hearing loss have been applied and most children accessed the CAMHS timely. To this aim synergism between hospital and territorial services, determining the implementation of the organization system was the keystone.